2018
DOI: 10.35906/vom.v5i07.16
|View full text |Cite
|
Sign up to set email alerts
|

Faktor - Faktor Yang Mempengaruhi Keputusan Masyarakat Terhadap Pemilihan Jasa Pelayanan Kesehatan Di Kecematan Latimojong Tahun 2016

Abstract: Health services are any efforts that are held personal or together within an organization to maintain and improve health, prevent, and cure diseases and restore the health of individuals, families, groups, or society. Buntu Sarek villageis is one village in the village Latimojong district with the general state of the topografi. Buntu Sarek village is a plateau area and the hills and located at an altitude between 600-2500 m above sea level. Health services are always concentrated in urban areas alone and whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The elevation variable plays a significant role in choosing hospitals for DHF patients in Purwosari District. This conclusion was similar to a study conducted in Latimojong, where facilities at 600-2500m asl experienced minimal visitors due to distance and low accessibility (Lolo and Julma, 2016). The number of doctors, accreditation, and the number of beds variables were also important factors in choosing hospitals.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The elevation variable plays a significant role in choosing hospitals for DHF patients in Purwosari District. This conclusion was similar to a study conducted in Latimojong, where facilities at 600-2500m asl experienced minimal visitors due to distance and low accessibility (Lolo and Julma, 2016). The number of doctors, accreditation, and the number of beds variables were also important factors in choosing hospitals.…”
Section: Resultssupporting
confidence: 87%
“…Several patients preferred closer hospitals due to short travel time, as they perceived shorter distances to increase safety (Vrangbaek et al, 2007). Similar studies in Latimojong demonstrated a significant effect of distance, culture, and sources of information on the choice of health services (Lolo and Julma, 2016). The long-distance factor implies limited options for health services.…”
Section: Resultsmentioning
confidence: 80%